ANALISIS PERBANDINGAN LINK STATE ADVERTISEMENT (LSA) TRAFFIC PADA OSPFV3 SINGLE AREA DAN MULTI AREA - , LATHIFAH FATHARANI, Sri Suning Kusumawardani, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Exhaustion of IPv4 address made a new addressing mechanism called IPv6. Those new mechanism also made new routing protocol, for example: OSPFv3. OSPFv3 is well-known and scalable routing protocol. Router in OSPFv3 use Link State Advertisement (LSA) to communicate with each other. But, if the topology getting large, it can cause enormous LSA flooding and make convergence time more slowly. OSPFv3 with multiple area (multi area) topology is designed to overcome those problem. This research will consider LSA traffic when the topology is configured in single area and multi area. The result is reduction of LSA number. Number of LSA reduction for an internal router which has non-summarized Area Border Router (ABR) is 37,93%. While number of LSA reduction for an internal router which has summarized ABR is 68,1%. It is proved that OSPFv3 multi area topology can reduce the number of LSA traffic.